The Mental Health of Black Youth Affected by Community Violence: Family and School Context as Pathways to Resilience - Donte T. Boyd; Kristian V. Jones; Camille R. Quinn; Adrian Gale; Ed-Dee G. Williams; Husain Lateef (MDPI AG, 2022)
Black youth who experience community violence occupy multiple environments with varying levels of influence on how they display resiliency to prevent adverse mental health outcomes. Considering the recent rise of mental health concerns (i.e., increase in suicidal outcomes) among Black youth, along with the abundance of research illustrating the detrimental impact of community violence, more research is needed to examine how different environmental factors (e.g., family and school) shape how youth protect their mental health while displaying resiliency navigating community violence. The purpose of this study was to examine how family and school contexts predict Black youths' ability to display resiliency to navigate community violence and prevent adverse mental health outcomes. This study utilized a path analysis to examine the associations between parent relationships, parent bonding, school climate, resilience to adverse community experiences, community violence, and mental health among 548 Black adolescents in Chicago. Findings highlight that parent relationships, parent bonding, and school climate influence the association between resilience to community violence and mental health outcomes among Black youth. Implications for mental health practice and policy among Black youth are discussed.